Kebangkitan Lima Karakter Orang Madura Pasca Corona - Ardhie Raditya; Naufalul Ihya’ Ulumuddin (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
The corona virus pandemic that has spread throughout the world, including Madura, has created a new normal for life in society. This new normal of life has an impact on the formation or strengthening of the character of the Madurese. There are five characters of Madurese who have strengthened the post-corona. Namely, the characters pènal, mertèh, ghetèh, nyarè bhâlâ, and ressè'. These five characters are a product of Madurese education which does not only come from schools or other formal educational institutions, but also a cultural process that has been going on for a long time in Madurese life. This paper aims to describe the five characters of Madurese after corona based on the perspective and research methods of social sciences and humanities.